POLA DAN GENESA STRUKTUR GEOLOGI PEGUNUNGAN SELATAN, PROVINSI DAERAH ISTIMEWA YOGYAKARTA DAN PROVINSI JAWA TENGAH - Prasetyadi, C.; Sudarno, Ign; Indranadi, VB.; Surono, Surono (Pusat Survei Geologi, 2011)
The geological structures in the study area are dominated by faults. The rest directions of the faults are northeast-southwest (16 faults) and north-south (14 faults). The remainder of faults are trending in northwest-southeast (3 faults) and west-east (3 faults) directions. Generally, the northeast-southwest and north-south trending faults are dominated by sinitral faults and a few of them are reactivated as normal faults. Whereas the northwest-southeast and west-east trending faults are mainly dextral and or normal faults.Key words: fault, sinitral, normal, and lineament